DNA Nanoribbon‐Templated Self‐Assembly of Ultrasmall Fluorescent Copper Nanoclusters with Enhanced Luminescence. (12th May 2020) - Ouyang, Xiangyuan; Wang, Meifang; Guo, Linjie; Cui, Chengjun; Liu, Ting; Ren, Yongan; Zhao, Yan; Ge, Zhilei; Guo, Xiniu; Xie, Gang; Li, Jiang; Fan, Chunhai; et al.
Abstract: Fluorescent copper nanoclusters (CuNCs) have been widely used in chemical sensors, biological imaging, and light‐emitting devices. However, individual fluorescent CuNCs have limitations in their capabilities arising from poor photostability and weak emission intensities. As one kind of aggregation‐induced emission luminogen (AIEgen), the formation of aggregates with high compactness and good order can efficiently improve the emission intensity, stability, and tunability of CuNCs. Here, DNA nanoribbons, containing multiple specific binding sites, serve as a template for in situ synthesis and assembly of ultrasmall CuNCs (0.6 nm). These CuNC self‐assemblies exhibit enhanced luminescence and excellent fluorescence stability because of tight and ordered arrangement through DNA nanoribbons templating. Furthermore, the stable and bright CuNC assemblies are demonstrated in the high‐sensitivity detection and intracellular fluorescence imaging of biothiols. Abstract : Ribbons and clusters : Individual copper nanoclusters (CuNCs) as building blocks are templated onto DNA nanoribbons to form compact and ordered CuNC self‐assemblies with strong and stable fluorescence. The assemblies have been used in the high‐sensitivity detection and intracellular fluorescence imaging of biothiols.